Boredom at School ? between Alienation and Emancipation - Stańczyk, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2012)
The article deals with the problem of boredom in education. The main purpose is to capture logic of misunderstandings between sides of learning processes. The article is organized by following questions: 1) How teachers comprehend phenomenon of boredom in their classroom? 2) Who should be blamed for boredom in education: teachers or pupils? 3) If boredom could have developmental potential? Answering the first question the writer accords with phenomenographical qualitative research procedure of examination meanings of school experiences imparted by pupils and their teachers. Boredom is one of keywords defining meaning of school and one of important issue which causes misunderstandings between pupils and teachers. The second question includes discussion on differentiation between causes of boredom during school-time and pupils’ free-time associated with psychological and sociological models of boredom. Psychological model of forced effort completed with analysis of its social conditions is considered as the most valid to capture the problem of responsibility for boredom appearing during school-time. In answer to the third question the writer considers ?epidemic of boredom? as a symptom of democratization and popularized presupposition that everyone has a right to fulfill their own life with meanings. To develop this assumption the author uses the analysis of boredom by Walter Benjamin and Martin Heidegger.